Literature Overview of the IL-17 Inhibition from Psoriasis to COVID-19 - Zou Y (Dove Medical Press, 2021)
Yulin Zou, Zudong Meng Department of Dermatology, Renmin Hospital, Hubei University of Medicine, Shiyan City, People’s Republic of ChinaCorrespondence: Zudong Meng Email zylmch1007@hbmu.edu.cnAbstract: The COVID-19 pandemic has posed a serious problem for drug anti-viral efficacy in combatting the cytokine storm triggered by SARS-CoV-2. From dermato-epidemiological studies conducted on psoriatic and other rheumatological patients, IL-17 inhibitors seem to attenuate or even prevent the cytokine storm and thus ICU referral. Furthermore, both in-vivo and in-vitro experiments suggest that IL-17 plays a key role in SARS-CoV-2 infection progression. Due to this evidence, we decided to summarize the literature findings on IL-17 inhibitors and COVID-19, maintaining psoriasis as the referral disease to better understand the extent of drug effects on the immune system.Keywords: biologics, COVID-19, psoriasis, therapy, IL-17